Analisis determinan produksi kopi di Kecamatan Kuala Betara Kabupaten Tanjung Jabung Barat - Deny Putra; Zulgani Zulgani; Parmadi Parmadi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This study aims to: 1) To determine and analyze the social and economic characteristics of coffee farmers in Kuala Betara District, Tanjung Jabung Barat Regency. 2) To determine and analyze the effect of land area, capital and labor on coffee production, Kuala Betara District, Tanjung Jabung Barat Regency by using multiple linear regression analysis tools. Based on the social and economic characteristics of Coffee Farmers in Kuala Betara District, Tanjung Jabung Barat Regency, it can be concluded that the average age of the Coffee Farmers is 39 years, the average number of dependents of Coffee Farmers is 2 dependents, the average working hours of Coffee Farmers is 3 hours, The average coffee production produced by coffee farmers is 57 kg, the average area of land owned by coffee farmers is 1.46 hectares, the average capital of coffee farmers is Rp. 187,400, the average workforce of Coffee Farmers is only 1 person and the average income of the respondents is Rp. 1,710,000 per month. Based on the results of multiple linear regression, it can be concluded that partially only the variables of land area and labor have a significant effect on coffee production in Kuala Betara District, Tanjung Jabung Barat Regency.